Escalation Of Coffee Plant (Coffea arabica L) By Addition Of Microcapsules From IAA (Indole Acetic Acid) Producing-Endophytic Bacteria - Purba, Indra Gunawan; Warsito, Kabul; Refnizuida, Refnizuida (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
The growth of coffee (Coffea arabica L) plants is highly dependent on the quality of the seeds and fertilization. One of the newest innovations in the field of organic farming is the use of endophytic bacteria as potential candidates to be developed become biofertilizers. Endophytic bacteria that produce IAA (Indole acetic acid) are able to produce phytohormones that can accelerate plant growth. The purpose of this researeh was to determine the effectiveness of endophytic bacterial microcapsules for the growth of Arabica coffee plants. This research was conducted using the factorial CRD (Completely Randomized Design) method consisting of 2 factors, 16 treatments, 2 replications. The first factor was  immersion  of endophytic bacterial suspension consisting of B0: without immersion; B1:8 hours; B2 :9 hours;  B3: 10 hours.  Microcapsules addition of endophytic bacteria consisting of I0 : 0 gr; I1 : 5 gr; I2 : 10 gr; I3 : 15 gr. The results from isolation was obtained four isolates of endophytic bacteria. The IAA test showed that the four  isolates were able to produce IAA. Observation of plant height showed that the best treatment was treatment B1 of (16.31 cm). Observation on total of leaves, best treatment were B1 and B2 (10.57 strands). For the leaf area parameter, the best treatment was B3 of (27.36 cm2). Test results showed that application of suspension and microcapsules of endophytic bacteria significantly increased growth of coffee